Quality Control Practices in a Tertiary Government Hospital Laboratory: Assessment of Documentation, Calibration, and Error Detection - Porca, Melrose; Dumangeng, Belma; Arellano, Erika Joyce; De Guzman, Camille; Marin, Elijah Wayne; Calistro, Rufo (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study evaluated the quality control (QC) practices of medical technologists in a tertiary government hospital laboratory in the Philippines, focusing on quality control documentation, equipment calibration, and analytical error detection, as well as the relationships among these domains and selected demographic variables. The study was conceptually anchored on the integrated nature of laboratory quality management, wherein documentation, calibration, and analytical error detection collectively support laboratory performance and compliance with quality standards. A descriptive–correlational research design was employed involving twelve licensed medical technologists selected through total enumeration. Data were collected using a structured, validated questionnaire and analyzed using weighted mean, standard deviation, Spearman rank correlation, Kruskal–Wallis test, and Cronbach’s Alpha at a 5% level of significance. The findings revealed very high levels of quality control documentation, equipment calibration, and analytical error detection practices among the respondents. No statistically significant relationships were found between quality control practices and respondents’ age, years of experience, or employment status. However, a very strong positive relationship was identified between quality control documentation and equipment calibration, indicating the interdependent nature of these quality management components. Due to the study’s small sample size, single-site setting, and reliance on self-reported measures, findings should be interpreted cautiously. The study concludes that quality control performance in the selected laboratory is supported by an integrated, systems-oriented approach. It recommends sustaining effective documentation, calibration, and analytical error detection practices while reinforcing the integration of documentation and calibration processes to promote continuous quality improvement. The study aligns with Sustainable Development Goal (SDG) 3: Good Health and Well-Being, SDG 9: Industry, Innovation and Infrastructure, and SDG 16: Peace, Justice and Strong Institutions by supporting reliable laboratory diagnostics, quality management systems, and adherence to recognized healthcare standards. Its findings contribute to public health, institutional, and innovation sustainability by providing evidence that may strengthen laboratory quality management and continuous quality improvement in government hospital laboratories.